PENERAPAN DISCOVERY LEARNING DENGAN MULTIMEDIA DALAM PENINGKATAN HASIL BELAJAR IPS PADA SISWA KELAS IV SDN 5 BUMIREJO TAHUN AJARAN 2015/2016 - Rhomartin, Wakid (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Discovery Learning Model Using Multimedia in Improving Social Science Learning for the Fourth Grade Students of SD Negeri 5 Bumirejo. The objectives of this research are: (1) to improve social science learning about economy activity and (2) to describe the steps on the application of discovery learning with multimedia. This research is a collaborative Classroom Action Research (CAR). Validity of data in this research was analyzed using triangulation of sources and triangulation of technique. Data were analyzed through data reduction, data display, and drawing conclusion or verification. The results of this research show that: (1) the application of discovery learning with multimedia can improve students? learning outcomes of social science and (2) the steps on the application of discovery learning with multimedia are as follows: orientation, problem statement, data collecting, data processing, verification, and generalization. Keywords: discovery learning, multimedia, learning, social science Abstrak: Penerapan Discovery learning dengan Multimedia dalam Peningkatan Hasil Belajar IPS Pada Siswa Kelas IV SDN 5 Bumirejo. Tujuan penelitian ini yaitu (1) meningkatkan hasil belajar IPS tentang aktivitas ekonomi; (2) mendeskripsikan langkah-langkah penerapan discovery learning dengan multimedia. Penelitian ini menggunakan penelitian tindakan kelas kolaboratif. Validasi data menggunakan triangulasi sumber dan teknik. Analisis data melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: (1)  penerapan discovery learning  dengan multimedia dapat meningkatkan hasil belajar siswa; (2) penerapan discovery learning dengan multimedia dilakukan dengan langkah-langkah: (a) orientation; (b) problem statement; (c) date collecting; (d) date processing; (e) verification: dan (f) generalization. Kata Kunci: discovery learning, multimedia, hasil belajar, IPS